Jacques Roux (le curé rouge) et le Manifeste des 'enragés' - Dommanget, Maurice (Paris : Spartacus, 1948)
Fonds Perrone
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Roux, Jacques; Franse Revolutie